2005
DOI: 10.1021/je050023z
|View full text |Cite
|
Sign up to set email alerts
|

VLE and LLE Data Set for the System Cyclohexane + Cyclohexene + Water + Cyclohexanol + Formic Acid + Formic Acid Cyclohexyl Ester

Abstract: The six-component system cyclohexene + water + cyclohexanol + cyclohexane + formic acid + formic acid cyclohexyl ester is currently being studied with the aim of carrying out the reaction of cyclohexene and water to cyclohexanol in a reactive distillation (RD) column. Because the direct reaction path of cyclohexene hydration is strongly limited by slow reaction rates with the known catalysts, an intermediate ester-formation step with formic acid was included in the studies. The challenge that this six-componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(50 citation statements)
references
References 3 publications
1
47
2
Order By: Relevance
“…In the second step, the ester readily hydrolyzes to produce cyclohexanol. Steyer et al 5,6,11 simulates the indirect hydration process using two distillation towers. Sulfonic-acid resin Amberlyst-15 catalyzed the esterication of cyclohexene with formic acid in the rst distillation tower, the hydrolysis of cyclohexyl formate occurred in the second column.…”
Section: Introductionmentioning
confidence: 99%
“…In the second step, the ester readily hydrolyzes to produce cyclohexanol. Steyer et al 5,6,11 simulates the indirect hydration process using two distillation towers. Sulfonic-acid resin Amberlyst-15 catalyzed the esterication of cyclohexene with formic acid in the rst distillation tower, the hydrolysis of cyclohexyl formate occurred in the second column.…”
Section: Introductionmentioning
confidence: 99%
“…points: ■, Barluenga et al; ×, Carlson et al. ; ⧫, Knight et al; ▲, Steyer et al; ●, this work; red solid line, parameters of Ant. eq, this work.…”
Section: Resultsmentioning
confidence: 80%
“…Unfortunately, the data for most of the systems are measured at a single temperature of 295 K (LLE measurements) or under atmospheric pressure (VLE measurements). Thus, the prediction of the data by the models , is limited for its use under different conditions, especially for VLE data due to a strong influence of temperature on the data. For this reason, a new VLE data set for CHOL + CHF system was performed in this work, and the data were fitted by NRTL and UNIQUAC models to prove the suitability of the published model , for data under lower pressures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many solid acid catalysts, such as silica-supported HPA (HSiW) or H 3 PW 12 O 40 , sulfated zirconia, and ion-exchange resins, have been used for the esterification of olefins with acids. [22][23][24] Amberlyst 15 is a commercially available, strongly acidic macroreticular polymeric resin based on crosslinked styrene, which is one of the most frequently used ion-exchange resins in acid-catalyzed reactions. 22 In particular, Saha and Sharma reported that Amberlyst 15 was more active than the Amberlite IR-120 genular resin, Engelhard F-24 acid-treated clay, and homogeneous p -toluene sulphonic acid catalysts in cyclohexene esterification with formic acid.…”
Section: Esterification Of Cyclohexene With Acetic Acidmentioning
confidence: 99%